IMPLEMENTASI KONSEP KAIZEN DALAM MENINGKATKAN KINERJA KARYAWAN - Amirullah -; Putria Dewi Masruroh (STIE Indonesia Malang, 2020)
This study aims to determine how the application of the concept of kaizen in improving employee performance at PT Surabaya Autocomp Indonesia in Mojokerto. Data collection is done by observation, interviews, and documentation. The method used is qualitative research. The research procedure was carried out through three stages, namely data reduction, 2) data display, and 3) conclusion or verification.The results showed that the implementation of the kaizen concept affected the performance of the employees of PT Surabaya Autocomp Indonesia. However, in applying the kaizen concept there are still a number of obstacles. The implementation of the kaizen concept is carried out by applying the 3M concept, the 5S concept, the PDCA concept (plan, do check, action), and the 5W + 1H concept. The effect of implementing the kaizen concept can be interpreted that to improve employee performance, companies can apply the kaizen concept effectively.Keywords: Kaizen Concept, Employee Performance